2017
DOI: 10.1128/aem.01419-17
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulator PhlH Modulates 2,4-Diacetylphloroglucinol Biosynthesis in Response to the Biosynthetic Intermediate and End Product

Abstract: Certain strains of biocontrol bacterium produce the secondary metabolite 2,4-diacetylphloroglucinol (2,4-DAPG) to antagonize soilborne phytopathogens in the rhizosphere. The gene cluster responsible for the biosynthesis of 2,4-DAPG is named and it is still unclear how the pathway-specific regulator within this gene cluster regulates the metabolism of 2,4-DAPG. Here, we found that PhlH in strain 2P24 represses the expression of the gene encoding the 2,4-DAPG hydrolase by binding to a sequence motif overlapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 48 publications
(62 reference statements)
2
57
0
Order By: Relevance
“…One example comes from the actinomycete Amycolatopsis mediterranei, in which rifamycin B (the endproduct of rifamycin biosynthesis) serves as an extracellular signaling molecule to regulate rifamycin export in a feedback mechanism (Lei et al, 2018). Another study showed that 2,4-diacetylphloroglucinol and its biosynthetic intermediate could serve as autoregulatory ligands to regulate its own biosynthesis in Pseudomonas fluorescens (Yan et al, 2017). These studies suggested that antibiotics and their biosynthetic intermediates could function as autoregulators to regulate their own biosynthesis, mainly through the modulation of the binding activity of CSRs to their target genes within their cognate gene clusters.…”
Section: Antibiotics and Their Biosynthetic Intermediates As Autoregumentioning
confidence: 99%
“…One example comes from the actinomycete Amycolatopsis mediterranei, in which rifamycin B (the endproduct of rifamycin biosynthesis) serves as an extracellular signaling molecule to regulate rifamycin export in a feedback mechanism (Lei et al, 2018). Another study showed that 2,4-diacetylphloroglucinol and its biosynthetic intermediate could serve as autoregulatory ligands to regulate its own biosynthesis in Pseudomonas fluorescens (Yan et al, 2017). These studies suggested that antibiotics and their biosynthetic intermediates could function as autoregulators to regulate their own biosynthesis, mainly through the modulation of the binding activity of CSRs to their target genes within their cognate gene clusters.…”
Section: Antibiotics and Their Biosynthetic Intermediates As Autoregumentioning
confidence: 99%
“…Finally, phlG encodes a hydrolase that specifically degrades 2,4-DAPG to less toxic MAPG and acetate [10]. Recent studies showed that another pathway-specific transcriptional repressor, PhlH, modulates 2,4-DAPG levels by controlling the expression of the phlG gene by sensing the concentration of 2,4-DAPG and MAPG in cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Plasmids for lacZ reporters in E. coli and P. fluorescens 2P24 were constructed using pSB1C3 and pRG970Km as previously described (Yan et al, ) and the primers used to amplify the DNA fragments are listed in Supporting Information Table S2. For lacZ assays in E.coli, the pSB1C3 derived plasmids were transformed into the E. coli DH5α strain and the bacteria were grown to an OD 600 of 0.6–0.8 in LB broth at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids for lacZ reporters in E. coli and P. fluorescens 2P24 were constructed using pSB1C3 and pRG970Km as previously described (Yan et al, 2017) and the primers used to amplify the DNA fragments are listed in Supporting Information Table S2. For lacZ assays in E. coli, the pSB1C3 derived plasmids were transformed into the E. coli DH5α strain and the bacteria were grown to an OD 600 of 0.6-0.8 in LB broth at 37 C. For lacZ assays in P. fluorescens 2P24, the pRG970Km derived plasmids were transformed into P. fluorescens 2P24 and conjugated to the wild-type strain and mutant strains by triparental mating using a helper strain (Finan et al, 1986).…”
Section: Construction Of Lacz Reporter Plasmids and β-Galactosidase Amentioning
confidence: 99%